2017
DOI: 10.1016/j.gaitpost.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Metric learning for Parkinsonian identification from IMU gait measurements

Abstract: Diagnosis of people with mild Parkinson's symptoms is difficult. Nevertheless, variations in gait pattern can be utilised to this purpose, when measured via Inertial Measurement Units (IMUs). Human gait, however, possesses a high degree of variability across individuals, and is subject to numerous nuisance factors. Therefore, off-the-shelf Machine Learning techniques may fail to classify it with the accuracy required in clinical trials. In this paper we propose a novel framework in which IMU gait measurement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Therefore, walking protocols and gait assessment systems materially impact on ML performance, which makes the comparison of previous ML studies inconclusive. In fact, previous literature has shown that, when using wearables to quantify gait, studies using 2 min CW protocols [18,19] achieved better results compared to those using 10m IW protocols [13,45]. In addition, studies showed that ML models derived from wearable inertial and force feet sensors [14,19,45,46] performed relatively better when compared to studies based on GAITRite data [17].…”
Section: Performance: An Overviewmentioning
confidence: 97%
“…Therefore, walking protocols and gait assessment systems materially impact on ML performance, which makes the comparison of previous ML studies inconclusive. In fact, previous literature has shown that, when using wearables to quantify gait, studies using 2 min CW protocols [18,19] achieved better results compared to those using 10m IW protocols [13,45]. In addition, studies showed that ML models derived from wearable inertial and force feet sensors [14,19,45,46] performed relatively better when compared to studies based on GAITRite data [17].…”
Section: Performance: An Overviewmentioning
confidence: 97%
“…Promising attempts to model and classify dementia and PD using measures of gait and postural control with a variety of classification tools (e.g., support vector machines, hidden Markov models, multilayer layer perception, neural networks, etc.) have been reported [163,164,165,167,168,169,170,171]. Even though the perfect classification accuracy is reported with various techniques, the optimal method or combination of approaches has not been identified, much less tested.…”
Section: Section Iii: Emerging Techniques For Disease Classificatimentioning
confidence: 99%
“…This approach resulted in a classification accuracy of 95.6%. In [68], IMU gait measurement sequences sampled during walking are encoded as hidden Markov models (HMMs) to extract their dynamics. The distance between HMMs is learned and employed in a standard nearest neighbour classifier.…”
Section: Related Workmentioning
confidence: 99%